أثر اكتشاف النار في تنمية ثقافات مجتمعات ما قبل التاريخ - حاج سعد, سليم; مياطه, التجاني (جامعة الوادي - University of Eloued, 2022)
تعد حدة اكتشاف النار بالنسبة لثقافات م ق ت كحدة الثورة الصناعية بإنجلترا في القرن 18م وما انجر عليها من تحولات عميقة في حياة المجتمعات والأمم على جميع الأصعدة، النار هو أهم الموضوعات لمعرفة تطور الانسان كيف اكتشفها في الطبيعة، فماذا وجد في الطبيعة حتى سهلت له معرفتها فيمكن القول أنه رأى انفجار بركاني وعرف هذا النموذج من الحرارة ، وأنه عرف النار في حد ذاته باحتراق الأعشاب والنبات ورأى أنها تلتهم الأخضر عرف مواد محترقة وبذلك وجد حيوانات محترقة واستعمل ذلك للطهي وهي إحدى الفوائد ويمكن ان يستغلها في أمور عديدة، فلاحظ النار مخيفة وكل الحيوانات تخاف النار ومن ثم يريد اكتساب النار لمحاربة الحيوان. The severity of the discovery of fire for the cultures of MQT such as the industrial revolution in England in the 18th century and the profound transformations in the lives of communities and nations at all levels, fire is the most important topics to know the evolution of man how he discovered in nature, what he found in nature so facilitated his knowledge It can be said that he saw a volcanic eruption and knew this form of heat, and that he knew the fire itself by burning the herbs and plants and saw that it devoured green knew burning materials and thus found burned animals and used it for cooking which is one of the benefits and can be exploited in many things, he observed the fire scary and all animals Afraid Fire and then wants to gain fire to fight the animal.
مقال
Keywords: اكتشاف النار، ثقافات ما قبل التاريخ، التطور الحضاري، الانسان البدائي، الغذاء; Fire Discovery, Prehistoric Cultures, Cultural Development, Neanderthal, Food